A dual-ratiometric optical thermometry based on Sr2LaF7:Er3+ crystal-implanted pliable fibers. Issue 20 (12th May 2022) - Li, C.; Li, Y.; Pun, E. Y. B.; Lin, H.
Abstract : Potential applications of composite fibers. Abstract : Sr2 (La1− x Er x )F7 /polyacrylonitrile composite fibers with special pliability and excellent crystal dispersibility have been fabricated, which provide smaller size and appropriate temperature sensitivity. Up-conversion emission shows quadratic dependence of the photoluminescence intensity on pump power, confirming the participation of two photons during the excitation processes. The composite fibers, combining main and auxiliary sensing derived from green and red emissions, give fibers the ability to obtain accurate results and better reproducibility. Among them, assigning the green emission as the main indicator of non-contact temperature sensing, the absolute and relative sensitivities are 0.514% K −1 and 0.654% K −1 at 373 K, respectively. Furthermore, the ratio of green and red emission serves as an auxiliary monitoring parameter to calibrate the deviation, where the absolute and relative sensitivities reach 7.208% K −1 and 0.901% K −1 at 373 K. In general, composite fibers with excellent dual-ratiometric temperature sensing are expected to be applied in biological probes, miniature devices and accurate temperature sensors.